Knowledge and attitudes about COVID-19 are associated with student compliance with health protocols - Lian Adhalia; Retno Sintowati (Universitas 'Aisyiyah Yogyakarta, 2023)
COVID-19 is a virus that spreads through droplet splashes that can remain active for several hours in the air. The main strategy to overcome the transmission of the covid-19 virus is to implement the COVID-19 protocol as a preventive effort. This study uses a cross-sectional research design with 134 respondents, with a sampling technique using simple random sampling. Data collection using Google form distributed via WhatsApp group. Data were processed using univariate, bivariate, and multivariate analysis. The chi-square test analysis showed a relationship between knowledge and attitudes about COVID-19 with compliance with the COVID-19 protocol with p 0.000 0.05. In contrast, the logistic regression test results showed a relationship between knowledge and attitudes about COVID-19 with compliance with the COVID-19 protocol with an R-Square value of 0.543. The conclusion that can be drawn from this study is that there is a relationship between knowledge and attitudes about COVID-19 with student health protocol compliance with OR values of 9.19 and 9.28, respectively, with an R-square value of 0.543. The contribution of the research is that students are expected to be able to apply health protocols correctly and consistently during covid-19.